MILLIY HÁM ULÍWMA INSANÍYLÍQ QÁDIRIYATLARDÍŃ OQÍWShÍLARDÍŃ QARÍM-QATNAS MÁDENIYATÍN ÚYRENIWDEGI ROLI - Esemuratova, T.A.; Matmuratova, G.K. (SCIENCE and SOCIETY, 2025)
The article examines the values of freedom, social justice, equality, truthfulness, enlightenment, beauty, honesty, intelligence, decency, behavior, humane relations and humane virtues in general, which serve the interests and goals of nations, peoples and social groups.